Penerapan Model Pembelaja RAN Kontekstual Meningkatkan Hasil Belajar Matematika Kelas III Di SDN Branggah II Kecamatan Lumbang - Ekawati Kusumastutik; Ludfi Arya Wardana; Didit Yulian Kasdriyanto (CV. ITTC INDONESIA, 2023)
Mathematics is a subject that is studied by all levels in education with a very important role in mastering science and technology. However, not all individuals have the ability in this mathematical matter. So that it is not uncommon for individuals to think that mathematics is a difficult subject. As was the case with the third grade students at SDN Branggah II, Lumbang District, their math skills were still relatively low. This means that there needs to be an action to fix the problem. Based on research, these problems occur because of the inappropriateness of the learning model used in learning mathematics. For this reason, researchers want to carry out an action to improve mathematics learning outcomes by utilizing the Contextual learning model. This research was carried out using classroom action research (PTK) with the data collection process using observation, tests and documentation. The data analysis process used is descriptive comparative data analysis and quantitative analysis. The use of Contextual learning models to improve student learning outcomes is very significant and effective, with the percentage of completeness in pre-cycle 37.5%, cycle I 61.5, and cycle II 87.9%. This means that here the utilization of this contextual learning model is very suitable for use in learning mathematics.